Questions   
Sort: 
 #1
avatar+1094 
+8

This involves casework. So, let's first see how many options there are for 5 digits:

This is basically 10 to the power of 5 (ten numbers from 0-9, and you can repeat, so 10(10)(10)(10)(10), which is 10^5), which is 100,000

(If you don't understand combinations, here is a link you could refer to: https://www.mathsisfun.com/combinatorics/combinations-permutations.html)

Same thing for 6, but 10^6, and you would get 1,000,000. Add those together, and you have 1,100,000.

 

(Not sure if you acctually read my explanation, or read this indecision, but here is a trickier practice problem for you (refer to website linked above if confused). Use the same problem that you stated above, BUT, instead, you can't repeat digits. (maybe not that much trickier, but you should try it.))

Jul 31, 2020
 #2
avatar
0
Jul 31, 2020
 #1
avatar+118667 
+1
Jul 31, 2020
 #1
avatar+26387 
+2

Using the Euclidian Algorithm, calculate \(\gcd(2^{60}-1, 2^{80}-1)\)

 

 

Formula: \( \boxed{ \gcd(a,b) = \gcd(b,a) \\~\\ \gcd(a,b) = \gcd(a-n*b,b) \\~\\ \gcd(a,a) = a }\)

 

 

\(\begin{array}{|rcll|} \hline && \mathbf{\gcd\left( 2^{60}-1,~ 2^{80}-1 \right)} \\ &=& \gcd\left( 2^{80}-1,~ 2^{60}-1 \right) \\ && \begin{array}{|rcll|} \hline 2^{80}-1 &=& 1+2+2^2+2^3+\ldots+2^{79} \\ 2^{60}-1 &=& 1+2+2^2+2^3+\ldots+2^{59} \\ \hline 2^{20}*(2^{60}-1) &=& 2^{20}+2^{21}+\ldots+2^{79} \\ \hline \mathbf{ (2^{80}-1)-2^{20}*(2^{60}-1)} &=& \mathbf{1+2+2^2+2^3+\ldots+2^{19}} \\ \mathbf{ (2^{80}-1)-2^{20}*(2^{60}-1)} &=& \mathbf{2^{20}-1} \\ \hline \end{array} \\ &=& \gcd\left( (2^{80}-1)-2^{20}*(2^{60}-1),~ 2^{60}-1 \right) \\ &=& \mathbf{ \gcd\left( 2^{20}-1,~ 2^{60}-1 \right) } \\ \hline \end{array}\)

 

\(\begin{array}{|rcll|} \hline && \mathbf{ \gcd\left( 2^{20}-1,~ 2^{60}-1 \right) } \\ &=& \mathbf{ \gcd\left( 2^{60}-1,~ 2^{20}-1 \right) } \\ && \begin{array}{|rcll|} \hline 2^{60}-1 &=& 1+2+2^2+2^3+\ldots+2^{59} \\ 2^{20}-1 &=& 1+2+2^2+2^3+\ldots+2^{19} \\ \hline 2^{40}*(2^{20}-1) &=& 2^{40}+2^{41}+\ldots+2^{59} \\ \hline \mathbf{ (2^{60}-1)-2^{40}*(2^{20}-1)} &=& \mathbf{1+2+2^2+2^3+\ldots+2^{39}} \\ \mathbf{ (2^{60}-1)-2^{40}*(2^{20}-1)} &=& \mathbf{2^{40}-1} \\ \hline \end{array} \\ &=& \gcd\left( (2^{60}-1)-2^{40}*(2^{20}-1),~ 2^{20}-1 \right) \\ &=& \mathbf{ \gcd\left( 2^{40}-1,~ 2^{20}-1 \right) } \\ \hline \end{array}\)

 

\(\begin{array}{|rcll|} \hline && \mathbf{ \gcd\left( 2^{40}-1,~ 2^{20}-1 \right) } \\ && \begin{array}{|rcll|} \hline 2^{40}-1 &=& 1+2+2^2+2^3+\ldots+2^{39} \\ 2^{20}-1 &=& 1+2+2^2+2^3+\ldots+2^{19} \\ \hline 2^{20}*(2^{20}-1) &=& 2^{20}+2^{21}+\ldots+2^{39} \\ \hline \mathbf{ (2^{40}-1)-2^{20}*(2^{20}-1)} &=& \mathbf{1+2+2^2+2^3+\ldots+2^{19}} \\ \mathbf{ (2^{40}-1)-2^{20}*(2^{20}-1)} &=& \mathbf{2^{20}-1} \\ \hline \end{array} \\ &=& \gcd\left( (2^{40}-1)-2^{20}*(2^{20}-1),~ 2^{20}-1 \right) \\ &=& \mathbf{ \gcd\left( 2^{20}-1,~ 2^{20}-1 \right) } \\ &=& 2^{20}-1 \\ &=& \mathbf{1048575} \\ \hline \end{array}\)

 

\(\begin{array}{|rcll|} \hline && \mathbf{\gcd\left( 2^{60}-1,~ 2^{80}-1 \right)} \\ &=& \mathbf{ \gcd\left( 2^{60}-1,~ 2^{20}-1 \right) } \\ &=& \mathbf{ \gcd\left( 2^{40}-1,~ 2^{20}-1 \right) } \\ &=& \mathbf{ \gcd\left( 2^{20}-1,~ 2^{20}-1 \right) } \\ &=& \mathbf{2^{20}-1} \\ &=& \mathbf{1048575} \\ \hline \end{array}\)

 

laugh

Jul 31, 2020
 #1
avatar+118667 
+3

\(y=\frac{1}{\sqrt2}-(x^2-3)\\ y=-x^2+3+\frac{1}{\sqrt2}\\ y=-x^2+\frac{6+\sqrt2}{2}\\ \)

 

This is a concave down parabola with y intercept     \(\frac{6+\sqrt2}{2}\approx 3.707\)

And the y axis is the axis of symmetry.

 

A general point on this parabola is    \((x,\left[-x^2+\frac{6+\sqrt2}{2}\right])\\\)

The distance square from (0,0) to the parabola for any given x value will be

 

\(d^2=D=(x-0)^2+(-x^2+\frac{6+\sqrt2}{2}-0)^2\\ D=x^2+(-x^2+\frac{6+\sqrt2}{2})^2\\ D=x^2+x^4+(-2*\frac{6+\sqrt2}{2})x^2+(\frac{6+\sqrt2}{2})^2\\ D=x^2+x^4+(-6-\sqrt2)x^2+(\frac{36+2+12\sqrt2}{4})\\ D=x^4+(1-6-\sqrt2)x^2+(\frac{19}{2}+3\sqrt2)\\ D=x^4+(-5-\sqrt2)x^2+(\frac{19}{2}+3\sqrt2)\\~\\ D'=4x^3+2(-5-\sqrt2)x\\ \text{D will be minimum when }D'=0\\ 0=4x^3+2(-5-\sqrt2)x\\ \text{I know just from thinking about the graph that }\;x\ne0\\ 0=4x^2+2(-5-\sqrt2)\\ 0=4x^2-10-2\sqrt2\\ 4x^2=10+2\sqrt2\\ 2x^2=5+\sqrt2\\ x^2=\frac{5+\sqrt2}{2}\\ x=\pm\sqrt{\frac{5+\sqrt2}{2}}\\\)

So the distance will be minimum when     \(x=\pm\sqrt{\frac{5+\sqrt2}{2}}\\\)

Sub to get y

 

\(y=-\left[\pm\sqrt{\frac{5+\sqrt2}{2}}\right]^2+\frac{6+\sqrt2}{2}\\ y=-\left[\frac{5+\sqrt2}{2}\right]+\frac{6+\sqrt2}{2}\\ y=\frac{-5-\sqrt2}{2}+\frac{6+\sqrt2}{2}\\ y=\frac{1}{2}\)

 

So the closest points on the parabola to (0,0)     are      \(\left(\sqrt{\frac{5+\sqrt2}{2}},\frac{1}{2}\right)\quad and \quad \left(-\sqrt{\frac{5+\sqrt2}{2}},\frac{1}{2}\right)\)

 

So the distance from either both these points to the origin will be    

 

 

\(d=\sqrt{          \left(\frac{5+\sqrt2}{2}\right)   + \frac{1}{4}       }\\ d=\sqrt{          \left(\frac{10+2\sqrt2+1}{4}\right) }\\ d=\sqrt{          \left(\frac{11+2\sqrt2}{4}\right) }\\ smallest\;\; distance=\frac{\sqrt{  11+2\sqrt2  }}{2}\\ smallest\;\; distance\approx 1.86\;units\)

 

Here is the related graph:

 

 

 

LaTex:

y=\frac{1}{\sqrt2}-(x^2-3)\\
y=-x^2+3+\frac{1}{\sqrt2}\\
y=-x^2+\frac{6+\sqrt2}{2}\\

 

d^2=D=(x-0)^2+(-x^2+\frac{6+\sqrt2}{2}-0)^2\\
D=x^2+(-x^2+\frac{6+\sqrt2}{2})^2\\
D=x^2+x^4+(-2*\frac{6+\sqrt2}{2})x^2+(\frac{6+\sqrt2}{2})^2\\
D=x^2+x^4+(-6-\sqrt2)x^2+(\frac{36+2+12\sqrt2}{4})\\
D=x^4+(1-6-\sqrt2)x^2+(\frac{19}{2}+3\sqrt2)\\
D=x^4+(-5-\sqrt2)x^2+(\frac{19}{2}+3\sqrt2)\\~\\
D'=4x^3+2(-5-\sqrt2)x\\
\text{D will be minimum when }D'=0\\
0=4x^3+2(-5-\sqrt2)x\\
\text{I know just from thinking about the graph that  }\;x\ne0\\
0=4x^2+2(-5-\sqrt2)\\
0=4x^2-10-2\sqrt2\\
4x^2=10+2\sqrt2\\
2x^2=5+\sqrt2\\
x^2=\frac{5+\sqrt2}{2}\\
x=\pm\sqrt{\frac{5+\sqrt2}{2}}\\

 

y=-\left[\pm\sqrt{\frac{5+\sqrt2}{2}}\right]^2+\frac{6+\sqrt2}{2}\\
y=-\left[\frac{5+\sqrt2}{2}\right]+\frac{6+\sqrt2}{2}\\
y=\frac{-5-\sqrt2}{2}+\frac{6+\sqrt2}{2}\\
y=\frac{1}{2}

 

\left(\sqrt{\frac{5+\sqrt2}{2}},\frac{1}{2}\right)\quad and \quad \left(-\sqrt{\frac{5+\sqrt2}{2}},\frac{1}{2}\right)

 

d=\sqrt{          \left(\frac{5+\sqrt2}{2}\right)   + \frac{1}{4}       }\\
d=\sqrt{          \left(\frac{10+2\sqrt2+1}{4}\right) }\\
d=\sqrt{          \left(\frac{11+2\sqrt2}{4}\right) }\\
smallest\;\; distance=\frac{\sqrt{  11+2\sqrt2  }}{2}\\
smallest\;\; distance\approx 1.86\;units

Jul 31, 2020

2 Online Users

avatar